How Economic Indicator Drive Crime? Empirical Study in Developing Country, Indonesia - Purnomo, Sodik Dwi; Supriyo, Doni Adi; Rusito, Rusito; Anindito, Teguh; Hariadi, Wahyu; Jati, Damar (International Journal of Economics and Financial Issues, 2023)
More offenses are committed in society as the crime rate rises, which is a sign that the safety of society is deteriorating. The purpose of this research is to examine how the Gini ratio, per capita income, unemployment, poverty, and population density affect the number of crimes committed in Indonesia between 2012 and 2020 in 34 Indonesian provinces, this research used secondary data from the years 2012 until 2020. Multiple linear regression using a panel data approach is the study methodology. The study’s findings demonstrate that the fixed effect approach is the most effective. Unemployment had a positive and significant impact on the amount of crimes, according to partial testing, while overcrowding and internet access had a negative and significant impact. In Indonesia between 2012 and 2020, the Gini ratio, per capita income, and poverty did not affect crime, according to partial testing, which also found that unemployment had a positive and significant impact on the number of crimes. Overcrowding and internet access also had a negative and significant impact on the number of crimes. According to this study, it is hoped that the government will establish learning facilities that put an emphasis on developing skills, offer counseling regarding family planning initiatives, and create a fair digital infrastructure to raise the standard of internet access.